2008
DOI: 10.1287/mnsc.1070.0771
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Policy for Software Vulnerability Disclosure

Abstract: Software vulnerabilities represent a serious threat to cyber security, most cyber-attacks exploit known vulnerabilities. Unfortunately, there is no agreed-upon policy for their disclosure. Disclosure policy (which sets a protected period given to a vendor to release the patch for the vulnerability) indirectly affects the speed and quality of the patch that a vendor develops. Thus CERT/CC and similar bodies acting in the public interest can use disclosure to influence the behavior of vendors and reduce social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 11 publications
0
71
0
Order By: Relevance
“…Only recently have researchers started investigating important economic questions in the area of information security. Our research is motivated by theoretical models of the relationship between the timing of vulnerability disclosure and the expected losses from attacks (Schneier, 2000;Arora et al, 2008;Cavusoglu et al, 2005) and more broadly research that has studied the factors shaping the timing and nature (public or private) of vulnerability disclosure by firms and third parties (Kannan and Telang, 2005;Nizovtsev and Thursby, 2007;Choi et al, 2005).…”
Section: Related Literature and Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently have researchers started investigating important economic questions in the area of information security. Our research is motivated by theoretical models of the relationship between the timing of vulnerability disclosure and the expected losses from attacks (Schneier, 2000;Arora et al, 2008;Cavusoglu et al, 2005) and more broadly research that has studied the factors shaping the timing and nature (public or private) of vulnerability disclosure by firms and third parties (Kannan and Telang, 2005;Nizovtsev and Thursby, 2007;Choi et al, 2005).…”
Section: Related Literature and Contributionmentioning
confidence: 99%
“…Even the release of a patch results in a temporary increase in attacks but a sharp decline thereafter, resulting in a lower average attack frequency. Arora et al (2008) use a dataset assembled from CERT/CC's vulnerability notes and SecurityFocus database to show that early disclosure leads to faster patch release times. Telang and Wattal (2007) use an event study methodology to show that vulnerability disclosure leads to a loss of market value.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for situations in which the actions of users impact upon the welfare of others, they develop a set of incentive structures for the implementation of effective patch management. The timing of vulnerability disclosures by vendors is modelled by [5], where it is shown that, with no regulation, the vendor releases a patch less frequently than is socially optimal. In [11], the relationship between the release of patches by vendors and their implementation by users is studied.…”
Section: Introductionmentioning
confidence: 99%
“…Arora, Telang, and Xu (2004) theoretically examine the optimal policy for software vulnerability disclosure. The software vendor strategy is limited to whether it will release a patch and if so when to release the patch.…”
Section: Examining Incentives For Software Vendorsmentioning
confidence: 99%